2022
DOI: 10.3390/ijms23031349
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Nature of Fragmentation of Human Embryos

Abstract: Embryo fragmentation represents a phenomenon generally characterized by the presence of membrane-bound extracellular cytoplasm into the perivitelline space. Recent evidence supports the cellular and molecular heterogeneity of embryo fragments. In this narrative review, we described the different embryo fragment-like cellular structures in their morphology, molecular content, and supposed function and have reported the proposed theories on their origin over the years. We identified articles related to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 119 publications
(160 reference statements)
1
19
0
2
Order By: Relevance
“…Blastomere exclusion is one phenomenon that could generate these fragments [33,34]. Recent time-lapse monitoring of embryo development has shown that blastomere exclusion is a common occurrence (64%) [34] Chromosomal analyses of these excluded blastocysts show a higher frequency of aneuploidy which is consistent with the hypothesis that this could be a mechanism of self-correction [33].…”
Section: Cellular Pathologysupporting
confidence: 69%
See 2 more Smart Citations
“…Blastomere exclusion is one phenomenon that could generate these fragments [33,34]. Recent time-lapse monitoring of embryo development has shown that blastomere exclusion is a common occurrence (64%) [34] Chromosomal analyses of these excluded blastocysts show a higher frequency of aneuploidy which is consistent with the hypothesis that this could be a mechanism of self-correction [33].…”
Section: Cellular Pathologysupporting
confidence: 69%
“…Fragmentation, also known as blebbing, occurs when a portion of an embryo's cell breaks off from the rest of the cell resulting in a membrane-bound cell fragment. Fragmentation may occur as early as the first embryo cell division [33]. Fragmentation is a common occurrence in embryos; however, high levels of fragmentation are associated with embryo loss.…”
Section: Cellular Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…It represents a safe and non‐invasive method used by several groups as a parameter to increase pregnancy rates 77 . The high level of fragmentation seen in the embryos sired from the MPH group is consistent with the poor chromatin structure of the sperm 78 . Adverse embryonic kinetics and embryonic genome instability were recently confirmed by single‐cell whole‐genome sequencing of individual blastomeres as a result of DNA fragmentation in bovine sperm caused by gamma‐radiation 79 …”
Section: Discussionmentioning
confidence: 80%
“…77 The high level of fragmentation seen in the embryos sired from the MPH group is consistent with the poor chromatin structure of the sperm. 78 Adverse embryonic kinetics and embryonic genome instability were recently confirmed by single-cell whole-genome sequencing of individual blastomeres as a result of DNA fragmentation in bovine sperm caused by gamma-radiation. 79 The protocol of treatment used in the present research-5 mg/kg of MPH per kilogram of body weight 80 -is considered within the average dose administered to humans.…”
Section: Discussionmentioning
confidence: 97%